Development, reliability, and validity of a self‐assessment scale for dementia care management. Issue 2 (1st February 2023) - Kazawa, Kana; Mochizuki, Mariko; Ochikubo, Hiroyuki; Ishii, Shinya
Abstract : Background: This study aimed to develop a self‐assessment scale for care management of people with dementia and examine its reliability and validity. Methods: Based on Bloom's Taxonomy, previous research, and experts' opinions on dementia and care management, a scale consisting of 18 items was developed to assess care managers' attitudes, knowledge, and skills in their management of people with dementia. To examine the scale's reliability and validity, data were collected from 638 care managers. Construct validity using exploratory factor analysis, known‐group validity, and internal consistency reliability of the scale were evaluated. Results: Exploratory factor analysis supported the construct validity with a four‐factor model and explained 59.1% of the total variance. Following were the four factors: Factor I 'Person centred care'; Factor II 'Understanding of disease characteristics, treatment and care'; Factor III 'Understanding of people with dementia and care management according to their characteristics'; and Factor IV 'Utilization of local resources surrounding people with dementia'. Regarding the known‐group validity, results showed that the group with a qualified chief care manager scored significantly higher than the group without one on Factors I ( P = 0.013) and III ( P = 0.026). Cronbach's alpha coefficient for the 18 items was 0.928. Conclusions: The findings prove that the scale has acceptable reliability and validity, and can help care managers reflect on their practice. Future research is desirable to measure the validation of change in the scale.